Religion, Identity and Power : Turkey and the Balkans in the Twenty-First Century - Öztürk, Ahmet Erdi (Edinburgh University Press, 2021)
This book examines Turkey's ethno-religious activism and power-related political strategies in the Balkans between 2002 and 2020, the period under the rule of the Justice and Development Party (AKP), to determine the scopes of its activities in the region.
Keywords: AK Parti (Turkey); Religion and politics -- Turkey.; Religion and politics -- Balkan Peninsula.; Turkey -- Foreign relations.; Balkan Peninsula -- Foreign relations.; Religion et politique -- Balkans.; Balkans -- Relations extérieures.; POLITICAL SCIENCE / Comparative Politics; Diplomatic relations; Religion and politics; Balkan Peninsula; Turkey